The Impact of Yoga Children on The Development of Toddlers - Astyandini, Budi; Khobibah, Khobibah; Isharyati, Septalia (Universitas Negeri Semarang, 2025)
Background: Child growth and development is an important task in preparing for human life. The incidence rate of fine motor disorders in preschoolers in the United States ranges from 12-16%, Thailand 24%, Argentina 22%, and in Indonesia between 13%-18%. Objective: To test the influence of yoga children on fine motor development and gross motor skills in toddlers in Patebon and Kendal Districts by 2024.Methods: This study used a quasi experiment method with a Pretest-Post test with a control group design. The population in this study is all early childhood aged 3 years in Patebon and Kendal Districts. Sampling using purposive sampling amounted to 40 children with 20 respondents in the intervention group and 20 respondents in the control group. The research location was conducted in early childhood in Patebon and Kendal Regencies. The research was conducted in October – December 2024. Results: The Mann-Whitney test was performed on both groups and the result was P Value = 0.010 meaning p < 0.05, meaning H0 was rejected and Ha was accepted. Conclusion: There is an effect of yoga on fine motor and gross motor development in 3-year-olds in Patebon and Kendal Districts in 2024. It is hoped that midwives will socialize the effectiveness of the Yoga method to improve the Development of Fine Motor and Gross Motor in Toddlers.